White matter integrity in older females is altered by increased body fat - Ryan, Lee (Obesity (Silver Spring), 2014)
OBJECTIVE: To assess whether the pattern of diffusion changes among a cohort of individuals showing BMI-related increases in white matter volume reflects healthy expansion of myelin or damaged white matter. DESIGN AND METHODS: Diffusion MRI measures (axial, radial, and fractional anisotropy) were obtained from 94 females, ages 52–92. Relationships between BMI and diffusion measures were assessed controlling for age, hypertension, and diabetes status using general linear modelling. Associations between diffusion measures and cognitive status (memory, executive functions, and visuomotor speed) were assessed using multiple regressions, controlling for age, education, hypertension, and diabetes status. RESULTS: Higher levels of BMI were associated with lower axial diffusion in frontal, temporal, parietal, internal capsule, and cerebellar white matter. Lower fractional anisotropy was observed in bilateral temporal white matter and the right corticospinal tract, with high radial diffusion in temporal and temporoparietal white matter. Importantly, diffusion measures predicted reductions in executive functioning, memory, and visuomotor speed. CONCLUSIONS: The pattern of diffusion changes in regions of white matter showing BMI-related volume increases are not due to expansion of normal myelin, but instead suggest damage to white matter that has important consequences for cognitive functioning.